The Tradition of Kenduri as a Means of Islamic Educational Values in Malay Society - Farah Nur Fadhilah; Nyayu Soraya; Baldi Anggara (Universitas Islam Negeri Sumatera Utara, 2026)
The Malay Society is an ethnic group with a strong identity in language, and cultural values formed by a long history of social, religious, and civilizational interactions, especially in the Malay Peninsula. The kenduri tradition as one of the cultural practices in Malay society is not a ceremonial ritual but plays a strategic role in pedagogical or educational matters as a means of character formation that takes place not only through formal institutions, but also through traditions and social practices of the community that instill spiritual educational values and social ethics that become the identity of the characteristics of the Malay society. This study uses a qualitative descriptive method approach (Literature review) with literature analysis and historical-cultural data searches from articles or previous studies to identify the function of the kenduri tradition in education in the life of Malay society. The results of this study indicate that the kenduri tradition contains spiritual educational and social values that function as a means of non-formal education that cannot be replaced by education through modern formal based on institutions.